OXA-48-like carbapenemases in the UK: an analysis of isolates and cases from 2007 to 2014. (10th February 2017) - Findlay, Jacqueline; Hopkins, Katie L.; Loy, Richard; Doumith, Michel; Meunier, Danièle; Hill, Robert; Pike, Rachel; Mustafa, Nazim; Livermore, David M.; Woodford, Neil
Abstract : Objectives: OXA-48-like carbapenemases have spread worldwide since 2001. We analysed patient and microbiological data for UK isolates with these enzymes as confirmed by the national reference laboratory from November 2007 to December 2014. Methods: MICs were determined using BSAC agar dilution. Isolates with reduced susceptibility or resistance to at least one carbapenem and high-level resistance to both piperacillin/tazobactam (MICs ≥64 mg/L) and temocillin (MICs ≥128 mg/L) were screened by PCR for bla OXA-48-like genes. The genomes of about half of the isolates were sequenced, with MLST types, resistance genes and plasmid replicon types inferred. Patient data provided by sending laboratories were reviewed. Results: Isolates ( n = 741) with OXA-48-like carbapenemases were submitted from 111 UK laboratories, representing 536 patients. Almost all (99%; 736 of 741) were Enterobacteriaceae, predominantly Klebsiella pneumoniae (55%; 408), and most (80%; 595) were from inpatients. WGS of 351 non-duplicate isolates identified bla OXA-48 as the most common variant, found in two-thirds (235 of 351) of isolates, followed by bla OXA-181 (68), bla OXA-232 (32), bla OXA-244 (10), bla OXA-484 (5) and bla OXA-245 (1). Among K. pneumoniae (163 of 351), Escherichia coli (114 of 351) and Enterobacter cloacae (42 of 351), 119 STs were identified. Mapping analyses revealed that 63% (222 of 351) of isolates harboured plasmids that shared >99% identity to one of four known plasmids [pOXA-48a (44%; 154 of 351), pOXA-232 (10%; 34 of 351), pOXA181 (9%; 30 of 351) and pKP3-A (1%; 4 of 351)]; the remaining 37% of isolates harboured bla OXA-48-like in unknown environments. Conclusions: OXA-48-like carbapenemases are an increasing problem in the UK. This study highlights both the role of successful plasmids and the polyclonal nature of their dissemination.